Long‐term outcome of re‐irradiation for recurrent or second primary head and neck cancer: A multi‐institutional study of AIRO—Head and Neck working group. Issue 10 (29th July 2019) - Orlandi, Ester; Bonomo, Pierluigi; Ferella, Letizia; D'Angelo, Elisa; Maddalo, Marta; Alterio, Daniela; Infante, Gabriele; Bacigalupo, Almalina; Argenone, Angela; Iacovelli, Nicola Alessandro; Desideri, Isacco; Meduri, Bruno; et al.
Abstract: Background: To report the long‐term outcome of patients undergoing re‐irradiation (re‐RT) for a recurrent or second primary head and neck cancer (RSPHNCs) in seven Italian tertiary centers, while testing the Multi‐Institution Reirradation (MIRI) recursive partitioning analysis (RPA) recently published. Methods: We retrospectively analyzed 159 patients. Prognostic factors for overall survival (OS) selected by a random forest model were included in a multivariable Cox analysis. To externally validate MIRI RPA, we estimated the Kaplan‐Meier group‐stratified OS curves for the whole population. Results: Five‐year OS was 43.5% (median follow‐up: 49.9 months). Nasopharyngeal site, no organ dysfunction, and re‐RT volume <36 cm 3 were independent factors for better OS. By applying the MIRI RPA to our cohort, a Harrell C‐Index of 0.526 was found indicating poor discriminative ability. Conclusion: Our data reinforce the survival benefit of Re‐RT for selected patients with RSPHNC. MIRI RPA was not validated in our population.